Konsep Pendidikan Islam Inklusif Perspektif KH. Abdurrahman Wahid - Rohmadi, Rohmadi; Yupi, Muarifah Novarini Yupi Novarini (Moderatio: Jurnal Moderasi Beragama, 2023)
Islamic inclusiveness is identical with the attitude of openness, tolerance and the spirit of cooperation both between adherents of Islam and with adherents of other religions. One of the big figures who initiated this is KH. Abdurrahman Wahid. To know the concept of inclusive Islamic education perspective according to KH. Abdurrahman Wahid and learning Islamic Education that is inclusive of current Islamic education. The type of research used in this research is library research. This research is a library research in which a lot of data collection is obtained through collecting data from various literatures. The literature studied is not limited to books or books, but is also obtained through documentation study materials, magazines, journals, and others. Meanwhile, the data analysis method used is content analysis. The results of this study state that the concept of Islamic education naturally should have an inclusive nature because Islam teaches respect for followers of other faiths and religions. Inclusive religion does not mean doubting their beliefs but accepting the existence of people of other religions/beliefs whose rights must be respected in society. With inclusive education, it is hoped that it will be able to foster a comprehensive view of students towards each other, make them aware that they are to cultivate an attitude of tolerance in differences.